STUDI KELAYAKAN USAHA TANI TEBU SISTEM BIBIT AWAL DIKECAMATAN PITU KABUPATEN NGAWI - Zahrul Yunus; Kusriani Prasetyowati; Mahananto Mahananto; Suswadi Suswandi (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2017)
Viewsofnaturalresources thatalargeanddiverse, theagricultural sectorhas apromosingfuture if can continue to be developed, the majority of the Indonesia population livelihood in agriculture.Todaytherearemanysomepeoplewho don’t understandtheexact methodof calculationof thecostof doingbusinessofagriculture.Farmingisn’tonlythecostbutalsotake intoaccountthefeasibility.Indonesiaiscountrythathas thepotensialtodevelopsugarcaneearly seedsystemproduction.Inthiscasebecausethenaturalresourceareownedandcanbeusedas aningredientsugarproduction.theresearch aimstodeterminethecost,revenue,income,and fesaybility of farming the sugarcane early seed system. The results of feasibility studies sugarcaneearly seed systemdistrictNgawi. Basicmethodusedthestudywas descriptive.ResearchlocationsindistrictofPitudistrict Ngawi,becausethatlocationisthelargestproducerof sugarcaneinngawi district.Datausedin thisresearcharesecondaryandprimarydata.To determinethecost offarming byadding variablecostandfixedcost,tofindrevenuebymultiplyingthetotalharvestandtotal cost, determinethefeasibilityoffarmingwithcalculations BEP,R/C,andµ/C. Resultsfeasibilitystudiessugarcaneindistrictof PitudistrictNgawi thatistotal costs Rp.80.908.806,00; revenueRp.115.425.000,00;incomeRp.34.516.193,9.Sugarcaneearly seed systeminditrictof PitudistrictNgawifeasibilitytobedevelopedbecauserevenue (Rp.115.425.000,00)>BEPrevenue(Rp.8.564.598,51),production (2.308,5kw)>BEP production (689,92kw)price (50.000/kw)BEPprice (35.048,21), R/C (1,42)≥1, µ/C (35,70%) >prevailing wage rate bank interest 12% revenue (Rp. 34.516.193,9) >land lease Rp. 14.637.679,7)labourproductivity(Rp.620.064,46)>prevailingwage rate(70.000).